ANALISIA PENGARUH CAMPURAN BAHAN BAKAR SOLAR-MINYAK JARAK PAGAR PADA KINERJA MOTOR DIESEL DAN EMISI GAS BUANG - Sumarsono, Markus (Jurnal Teknologi Lingkungan, 2008)
A test of a diesel motor using the fuel mixture of diesel-jatropha oil has been conducted in order to analyze the influence of fuel mixture composition to the motor performance and exhaust gas emission. The motor which had a single cylinder, 4 cycles, with maximum energy output of 4.4 kW at 2600 rpm, moved agenerator as electricity power load. The percentage of jatropha oil in fuel mixture was 0%, 10%, 30%, 50% and 100%. The testing method was, to each fuel mixture composition and at constant 2000 rpm motor rotation with electricity power load of 0 and 2 kW, the data concerning to the fuel consumption, lubricating oiltemperature and exhaust gas emission was measured. The test result indicated that the higher the percentage of jatropha oil in fuel mixture, the higher the fuel consumption and the CO2 and NOx emission in exhaust gas, but the lower the HC and O2 emission and opacity of exhaust gas.